EKSISTENSI PERADILAN PIDANA TERHADAP JAMINAN DAN PERLINDUNGAN SAKSI KORBAN DALAM KASUS PIDANA - Munte, Gaya pesona; Husna, Lenny (SCIENTIA JOURNAL, 2024)
This research examines the existence of criminal justice in providing physical, legal and psychological protection to victim witnesses in criminal cases. The main challenges faced by victim witnesses, including threats, intimidation, and other obstacles, are the focus of this research. The criminal justice system must address this challenge seriously through effective witness protection programs, strict law enforcement against perpetrators of threats, and the provision of adequate psychological support and legal aid. Reforms in the broader criminal justice process also need to be considered to improve justice and protection for victim witnesses. Understanding this issue is important in efforts to maintain the integrity of the legal system and provide better protection for individuals involved in the criminal justice process.   Keywords: existence of criminal justice, victim witness protection, threats, intimidation, obstacles, witness protection program, criminal justice reform.